Automatic mapping tasks to cores : Evaluating AMTHA Algorithm in multicore architectures - De Giusti, Laura Cristina (2009)
The AMTHA (Automatic Mapping Task on Heterogeneous Architectures) algorithm for task-to-processors assignment and the MPAHA (Model of Parallel Algorithms on Heterogeneous Architectures) model are presented. The use of AMTHA is analyzed for multicore processor-based architectures, considering the communication model among processes in use. The results obtained in the tests carried out are presented, comparing the real execution times on multicores of a set of synthetic applications with the predictions obtained with AMTHA. Finally current lines of research are presented, focusing on clusters of multicores and hybrid programming paradigms